Lidar estimates of birch pollen number, mass, and CCN-related concentrations - Filioglou, Maria; Tiitta, Petri; Shang, Xiaoxia; Leskinen, Ari; Ahola, Pasi; Patsi, Sanna; Saarto, Annika; Vakkari, Ville; Isopahkala, Uula; Komppula, Mika (Copernicus GmbH, 2025)
The accurate representation of microphysical properties of atmospheric aerosol particles - such as the number, mass, and cloud condensation nuclei (CCN) concentration - is key to constraining climate forcing estimations and improving weather and air quality forecasts. Lidars capable of vertically resolving aerosol optical properties have been increasingly utilized to study aerosol-cloud interactions, allowing for estimations of cloud-relevant microphysical properties. Recently, lidars have been employed to identify and monitor pollen particles in the atmosphere, an understudied aerosol particle with health and possibly climate implications. Lidar remote sensing of pollen is an emerging research field, and in this study, we present for the first time retrievals of particle number, mass, CCN, giant CCN (GCCN), and ultragiant CCN (UGCCN) concentration estimations of birch pollen derived from polarization lidar observations and specifically from a PollyXT lidar and a Vaisala CL61 ceilometer at 532 and 910 nm, respectively.A pivotal role in these estimations is played by the conversion factors necessary to convert the optical measurements into microphysical properties. This set of conversion parameters for birch pollen is derived from in situ observations of major birch pollen events at Vehmasm & auml;ki station in eastern Finland. The results show that under well-mixed conditions, surface measurements from in situ instrumentation can be correlated with lidar observations at higher altitudes to estimate the conversion factors. Better linear agreement to the in situ observations was found at the longer wavelength of 910 nm, which is attributed to a combination of lower overlap and higher sensitivity to bigger particles compared to observations at 532 nm. Then, the conversion factors are applied to ground-based lidar observations and compared against in situ measurements of aerosol and pollen particles. In turn, this demonstrates the potential of ground-based lidars such as a ceilometer network with the polarization capacity to document large-scale birch pollen outbursts in detail and thus to provide valuable information for climate, cloud, and air quality modeling efforts, elucidating the role of pollen within the atmospheric system.